2018
DOI: 10.1080/2162402x.2018.1502904
|View full text |Cite
|
Sign up to set email alerts
|

CD27 stimulation unveils the efficacy of linked class I/II peptide vaccines in poorly immunogenic tumors by orchestrating a coordinated CD4/CD8 T cell response

Abstract: Despite their promise, tumor-specific peptide vaccines have limited efficacy. CD27 is a costimulatory molecule expressed on CD4+ and CD8+ T cells that is important in immune activation. Here we determine if a novel CD27 agonist antibody (αhCD27) can enhance the antitumor T cell response and efficacy of peptide vaccines. We evaluated the effects of αhCD27 on the immunogenicity and antitumor efficacy of whole protein, class I-restricted, and class II-restricted peptide vaccines using a transgenic mouse expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A previous study using a novel CD27 agonist antibody (αhCD27) and peptide vaccine showed their efficacy on active cancer immunotherapy. 46 Furthermore, PD-1 blockade and CD27 stimulation activated and synergized CD8 + T-cell-driven antitumor immunity in multiple tumor models. 47 CD70–CD27 interactions are important for the regulation of adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using a novel CD27 agonist antibody (αhCD27) and peptide vaccine showed their efficacy on active cancer immunotherapy. 46 Furthermore, PD-1 blockade and CD27 stimulation activated and synergized CD8 + T-cell-driven antitumor immunity in multiple tumor models. 47 CD70–CD27 interactions are important for the regulation of adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we asked whether T-cell helper function could be effectively provided by using a universally immunogenic helper epitope. For this question, we utilized the highly immunogenic supertope P30 from tetanus toxin, which (1) contains MHC II-restricted epitopes that bind to the majority of MHC II haplotypes, (2) leverages population-wide T-cell memory to tetanus toxin, providing a sufficient pool of CD4+ T-cell precursors, and (3) has been shown to be safe in humans 13 15 . When P30 and Odc1 MHC I were administered into mice as separate peptides, no substantial IFNγ Odc1 MHC I CTL response or antitumor effects were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this hypothesis, we have previously found that SIINFEKL-specific CD8+ T cells are present in untreated, intracerebrally implanted B16 melanoma tumors expressing ovalbumin (B16OVA) 26 , but a vaccine composed of SIINFEKL conjoined to P30 (SIINFEKL-P30) is ineffective, on its own, against intracerebral B16OVA tumors—analogous to our findings with the Odc1 neoantigen in SMA560. However, when SIINFEKL-P30 is administered in conjunction with an agonist antibody targeting the T-cell costimulatory molecule CD27, a significant survival benefit against intracerebral B16OVA tumors is observed 13 . Additional supporting evidence has come from another study showing that coadministration of anti-PDL1 antibody is capable of unleashing the antitumor effects of a polyvalent neoantigen vaccine against intracerebral CT2A 27 , an aggressive mouse brain tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma patients may be repeatedly pancytopenic for periods of time due to chemotherapy-induced myelosuppression and myeloablation, exposing them to the risk of infection and limiting mechanisms of innate anti-tumor immunity (Table 1 ). The most commonly used chemotherapeutic in glioma treatment is temozolomide, a DNA methylator that is known to cause long-lasting lymphopenia [ 84 , 85 ]. Additionally, the use of temozolomide is associated with an upregulation of T-cell exhaustion markers such as LAG-3 and TIM-3, which has unique implications for its concomitant use with immunotherapy [ 86 ].…”
Section: Systemic/treatment-related Immune Suppressionmentioning
confidence: 99%
“…While these negative chemotherapy-induced side effects are well noted and should be minimized whenever possible, a recently-devised strategy uses the lymphotoxicity of temozolomide to the clinician’s advantage within a specific treatment paradigm. Suryadevara and colleagues were able to utilize a dose-intensified temozolomide regimen to deplete host lymphocytes prior to CAR administration, which was associated with dramatically improved CAR proliferation, complete tumor regression, and increased survival in a murine model of GBM [ 84 ]. Examples such as this one highlight the ability of clinicians and researchers to develop innovative and/or unconventional uses of traditional chemotherapeutics to enhance antitumor immunity.…”
Section: Systemic/treatment-related Immune Suppressionmentioning
confidence: 99%